Development of a Protein Concept Inventory: A Proposal for Item Scoring and Responding - Taşçi, Güntay (Science Insights Education Frontiers, 2024)
The present study has aimed to develop and validate a protein concept inventory (PCI) consisting of 25 multiple-choice (MC) questions to assess students’ understanding of protein, which is a fundamental concept across different biology disciplines. The development process of the PCI involved a literature review to identify protein-related content, validation interviews to iteratively validate and refine the created items (n = 26), and data collection from a large sample (n = 291) for statistical analysis. An expert interview was held with two different field experts regarding the content validity of the draft PCI tool, the suitability of the options, and the clarity of the items. Free choice format (multiple marking) was used to answer the developed MC items. In scoring these items, positive points were given to correct options, and negative points were given to incorrect options. Evidence regarding the psychometric properties of the PCI trial form was collected through factor analysis, group differentiation, internal consistency, and item analysis using quantitative data. The evidence collected demonstrates that the validity and reliability of the PCI as a measurement tool have been confirmed. PCI’s scoring approach and the use of response patterns created by multiple markings in teaching are discussed.